Improving UX problem solution through divergent and convergent design thinking in UX journey - Kusuma, Wahyu Andhyka; Jantan, Azrul Hazri; Mohd Norowi, Noris; Admodisastro, Novia Indriaty (IEEE, 2023)
Design solves the problem because the design positively correlates with performance improvement and simplifies some problems. Design thinking is a formal solution that solves problems creatively to increase product innovation. Frequently, to create solutions, developers will see from the perspective of products that are already on the market or use the latest technology to create design solutions; however, design thinking is a solution that uses the creativity of developers to create opportunities based on creativity from what already exists and can imagine the novelty of the product. The contradiction between solution and direction innovation emphasizes that both require variant design thinking practices. This research investigates several issues (i) the relationship between design thinking practices and constructs a value from a problem, and (ii) how to increase the value of this relationship to be moderated when the goal is determined to be solution innovation or direction innovation. This research contributes to providing increased value from the relationship between solution innovation and direction innovation according to the context of the problems faced. Moreover, developers can determine creative solutions that have value from a problem. By involving 137 freelance developers, researchers succeeded in proving that the UX Journey, a flexible design thinking-inspired model, can show that there is a positive relationship between the practice of user need elicitation and the value generated through design thinking is stronger for solution innovation than for direction innovation, with an average value of the solution is one (0.9136).